2004
DOI: 10.3748/wjg.v10.i20.2949
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic spread of low rectal cancer in regions of mesorectum: Pathologic assessment with whole-mount sections

Abstract: AIM:To assess the microscopic spread of low rectal cancer in mesorectum regions to provide pathological evidence for the necessity of total mesorectal excision (TME). METHODS:A total of 62 patients with low rectal cancer underwent low anterior resection and TME, surgical specimens were sliced transversely on the serial embedded blocks at 2.5 mm interval, and stained with hematoxylin and eosin (HE). The mesorectum on whole-mount sections was divided into three regions: outer region of mesorectum (ORM), middle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…5 mm in diameter are more often involved by the tumor than bigger ones. Such findings pinpoint the importance of TME [24][25][26] . The pathologist must differentiate the peritonealized from non-peritonealized surfaces of the resection.…”
Section: Circumferential Resection Marginmentioning
confidence: 88%
“…5 mm in diameter are more often involved by the tumor than bigger ones. Such findings pinpoint the importance of TME [24][25][26] . The pathologist must differentiate the peritonealized from non-peritonealized surfaces of the resection.…”
Section: Circumferential Resection Marginmentioning
confidence: 88%
“…Involvement of the lateral resection margins correlates with a bad prognosis and is a prognostic factor for local recurrence. 12 42 43 These results led us to consider tumour regression grading and the depth of neoplastic infiltration within the perirectal fat as new important prognostic factors for rectal cancer that should be evaluated, after combined neoadjuvant CRT and surgery, in order to plan better therapeutic strategies based on a quantitative evaluation of the response to neoadjuvant treatment and the extent of tumour involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] The technique of total mesorectal excision (TME) places great importance on the anterior and posterior planes of resection, but little information is available about the lateral resection margins, which are known to be important determinants of loco-regional recurrence. 12 13 15 16 Surgery for rectal cancer has almost gone full circle. 12 13 17 First there was a 5 cm rule, which was reduced to 2 cm because it was shown that intramural spread was confined within this border except in the most advanced disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of nodal metastasis in the mesorectum distal to the primary tumor occurs in up to 20% of patients. Most of these metastases are located within 2 cm from the lower margin of the primary tumor; nodal metastases beyond 4 cm are exceptional [81][82][83].…”
Section: Patterns Of Metastasis In Colorectal Cancermentioning
confidence: 99%